2013
DOI: 10.7243/2052-5966-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional education and lifestyle modification on the nutritional status of HIV positive patients: results of a cluster randomized intervention over a period of six months

Abstract: Background: Effective strategies to improve nutritional status exist, though short-termed and less sustainable for HIV patients in resource limited settings. The aim of this study was to describe the BMI of treatment naïve HIV patients in Yaoundé, Cameroon, and investigate the effects of nutritional education and lifestyle modification on the nutritional status of these patients. Method: A cluster randomized trial was conducted between 2010 and 2012, and included 5 health facilities, randomized either to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…We identified 12 unique studies (Figure 1) that examined the influence of nutrition education and counselling on the occurrence of important clinical outcomes among PLHIV. These studies were either RCTs [28][29][30], cluster RCTs [7,31], pre-post interventional studies [22,31,32] or pre-post interventional studies based on one arm of an RCT [33][34][35]. All studies were conducted among adults.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 12 unique studies (Figure 1) that examined the influence of nutrition education and counselling on the occurrence of important clinical outcomes among PLHIV. These studies were either RCTs [28][29][30], cluster RCTs [7,31], pre-post interventional studies [22,31,32] or pre-post interventional studies based on one arm of an RCT [33][34][35]. All studies were conducted among adults.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…In one study, a caregiver was required to be present. Most studies did not specify who delivered the intervention [7,22,28,31,[34][35][36]. In one study, nutrition counselling was delivered by a peer [31].…”
Section: Counselling/education Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated spirulina's beneficial effects and therapeutic functions [ 22 23 ]. Other studies have shown that spirulina has beneficial effects on the treatment of malnutrition and other pathologies such as obesity, hypercholesterolemia, hypertension, and diabetes mellitus [ 24 25 26 ]. Studies have reported spirulina was associated with modulation of the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated beneficial effects of S. platensis in vitro and in vivo as well as its therapeutic functions [ 13 , 14 ]. In addition, some studies show that spirulina has beneficial effects on the treatment of malnutrition and on other pathologies such as obesity, hypercholesterolaemia, arterial hypertension and diabetes mellitus [ 15 – 17 ]. This study was performed, to assess the potential effects of 10 grams of daily supplementation of S. platensis with a local balance diet on the level of CD4 cells count and viral load during six months by treatment naïve HIV–infected persons.…”
Section: Introductionmentioning
confidence: 99%